High-performing laminated perovskite solar cells by surface engineering of perovskite films - Gong, Oh Yeong; Seo, Min Kyeong; Choi, Jin Hyuk; Kim, So Yeon; Kim, Dong Hoe; Cho, In Sun; Park, Nam Gyu; Han, Gill Sang; Jung, Hyun Suk (Applied Surface Science, 2022)
Stacked perovskite films—laminated films in particular—have garnered considerable attention owing to their excellent potential for various applications. However, perovskite solar cells fabricated using laminated perovskite films exhibit a critically low power conversion efficiency. To overcome this limitation, in this paper, we report the surface and grain boundary engineering of perovskite films via transfer printing using the hot-pressing process to attain high-performing laminated perovskite solar cells. Perovskite films whose surface and grain boundaries were selectively dissolved by acetonitrile exhibited suppressed formation of defects at the lamination interface, and uniform plastic deformation was induced in the films during the hot-pressing process. Consequently, high efficiency of 22.52% and high intrinsic stability, namely the retention of an average of 96% of the initial efficiency after 2000 h, were achieved.
Keywords: Hot-pressing process; Laminated films; Laminated perovskite solar cell; Lamination of perovskite film; Low Power; Perovskite films; Power conversion efficiencies; Surface boundaries; Surface engineering; Transfer printing; Hot-pressing; Laminated perovskite solar cells; Lamination of perovskite film; Surface engineering; Transfer printing